Performance of the ARC-HBR criteria in ST-elevation myocardial infarction. Significance of smoking as an additional bleeding risk factor - Kesti, Henri; Mattila, Kalle; Jaakkola, Samuli; Lehto, Joonas; Söderblom, Nea; Kalliovalkama, Kalle; Porela, Pekka (Oxford University Press (OUP), 2025)
Background and aims: The Academic Research Consortium for High Bleeding Risk Criteria (ARC-HBR) are recommended by guidelines for bleeding risk assessment in ST-elevation myocardial infarction (STEMI). The aim of this study was to identify possible other risk factors and adjust the original ARC-HBR criteria for confounders.
Methods: All consecutive STEMI patients managed in a Finnish tertiary hospital between 2016-2022 were identified using a database search. Data collection was done by reviewing electronic patient records. Bleeding risk was assessed according to the ARC-HBR criteria. The primary endpoint was non-access site bleeding academic research consortium (BARC) type 3 or 5 bleeding during 1-year follow-up.
Results: A total of 1548 STEMI patients were analysed. HBR criteria was fulfilled in 661 (42.7%). Multivariable competing risk analysis identified only 4 individual ARC-HBR criteria as independent risk factors for bleeding. Smoking status was identified as a novel bleeding risk factor. Current and former smokers had increased bleeding risk compared with never smokers (hazard ratio [HR] 3.01, 95% confidence interval [CI] 1.62-5.61 and HR 1.99, CI 1.19-3.34). In those not meeting any ARC-HBR criteria, cumulative BARC 3 or 5 incidence of current smoking was 3.40% and intracranial haemorrhage (ICH) 1.36%. Thus, exceeding ARC-HBR definition for a major criterion. In the non-HBR group the prevalence of current smoking was 40.4% (n = 358).
Conclusions: Current and former smoking predicts major bleeding complications after STEMI. Current smoking is highly prevalent among those classified as non-HBR according to the ARC-HBR criteria.